Technology-Based Solar System Learning Media For Grade 6 Elementary School Students - Handriana Naurah Ihram; Wahyu Kurniawati (Sean Institute, 2024)
The Solar System is a lesson that teaches various knowledge about the collection of celestial bodies consisting of a star called the Sun and all objects bound by its gravity. However, because many of the lessons implemented today still rely on traditional learning, students' interest in participating in this lesson is still low. Replacing this learning model with a more active, creative, effective and fun learning model to increase student interest in learning, improve student learning outcomes, increase student development activities and build existing potential, so that it is expected to increase the potential.